A comparison of the efficiency of RNA extraction from extracellular vesicles using the Qiagen RNeasy MinElute versus Enzymax LLC RNA Tini Spin columns and qPCR of miRNA. Issue 1 (21st July 2021) - Dunlop, Rachael Anne; Banack, Sandra Anne; Cox, Paul Alan
Abstract: One consequence of the current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is an interruption to the supply of laboratory consumables, particularly those used for RNA extraction. This category includes column-based RNA extraction kits designed to retain short RNA species (defined as having fewer than 200 nucleotides), from small sample volumes, e.g. exosomes or extracellular vesicles (EVs). Qiagen manufactures several kits for the extraction and enrichment of short RNA species, such as microRNA (miRNA), which contain silica-membrane columns called "RNeasy MinElute Spin Columns." These kits, which also contain buffers and collection tubes, range in price from USD380 to greater than USD1000 and have been subject to fulfillment delays. Scientists seeking to reduce single-use plastics and costs may wish to order the columns separately; however, Qiagen does not sell the RNeasy MinElute Spin Columns (in reasonable quantities) as an individual item. Thus, we sought an alternative product and found RNA Tini Spin columns from Enzymax LLC. We conducted a systematic comparison of the efficiency of RNA extraction for miRNA quantitative real-time PCR (qPCR) using the Qiagen RNeasy MinElute Spin Columns and Enzymax LLC RNA Tini Spin columns and the Qiagen total RNA extraction protocol that enriches for short RNA species. We compared the efficiency of extraction of five spike-in control miRNAs, six sample signal miRNAs, and nine low- to medium-abundance miRNAs by qPCR. The RNA was extracted from EV preparations purified from human plasma using CD81 immunoprecipitation. We report no statistically significant differences in extraction efficiencies between the two columns for any of the miRNAs examined. Therefore, we conclude that the Enzymax RNA Tini Spin columns are adequate substitutes for the Qiagen RNeasy MinElute Spin Columns for short RNA species enrichment and downstream qPCR from EVs in the miRNAs we examined.